Something Greater Than Ourselves: Towards Good Academic Management - Kociatkiewicz, Jerzy; Kostera, Monika (Stan Rzeczy, 2024)
Universities have been with us for centuries if not millennia. The academy is one of the oldest organisational forms still in existence. Throughout their history, universities have evolved, experimenting with various kinds of organisational structure: from student association, through private company, to ecclesiastical, state, or local government institution. They have been continually altering their management structure: from a collective of peers through a centralised hierarchy and a loose federation of faculties to a structure based on deeply democratic collegiality. Currently in Poland, as in many other countries, a series of reforms have put universities under pressure to “marketise.” This paper discusses some of the urgent dilemmas that have arisen after the transformation of the sector and offers some ideas for where sustainable managerial solutions could be sought.